Bulldog decision. Issue 2 (24th December 2021) - Cyphers, Travis Lee; Apodaca, Julianne Renee
Abstract : Theoretical basis: The theoretical basis for this case is a focus on ethical decision-making based upon a decision-making tree proposed by Bagley et al. (2003). Once multiple options are determined as ethical, integrating authentic leadership into the decision-making process can help leaders made difficult decisions. Research methodology: The authors conducted extensive research through IBISWorld, EBSCOhost, and academic journals to review ethical decision-making and authentic leadership. The authors successfully piloted the case with over 100 undergraduate and graduate students enrolled in leadership courses. Case overview/synopsis: The case describes an ethical decision a young commanding officer must make. A soldier under their leadership has been charged with an inappropriate relationship with a minor. The officer must decide between two actions that are legal within the military justice system. Each decision has ramifications that will significantly affect the organization. Complexity academic level: The case is best taught in undergraduate and graduate leadership courses. Course participants do not need a detailed understanding of military leadership or military law to apply fundamental concepts.